2013
DOI: 10.1002/ar.22763
|View full text |Cite
|
Sign up to set email alerts
|

Allen's Rule Revisited: Temperature Influences Bone Elongation During a Critical Period of Postnatal Development

Abstract: Limbs of animals raised at warm ambient temperature are significantly and permanently longer than those of siblings housed in the cold. These highly reproducible lab results closely parallel the ecogeographical tenet described by Allen's extremity size rule, which states that appendage length correlates with temperature and latitude. It is unclear what mechanisms underlie these differences and in what pattern they emerge, since the morphology is traditionally thought to reflect naturally selected genomic adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 83 publications
(93 reference statements)
2
22
0
1
Order By: Relevance
“…In support of this view, it has been shown that environmental temperature irreversibly regulates appendage length and body mass at a critical time of neonatal development (Serrat, 2013; Serrat, King, & Lovejoy, 2008; Weaver & Ingram, 1969). That is, Allan's and Bergman's rules are strongly influenced by epigenetic factors, within the bounds of a species' overall phylogenetic traits.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In support of this view, it has been shown that environmental temperature irreversibly regulates appendage length and body mass at a critical time of neonatal development (Serrat, 2013; Serrat, King, & Lovejoy, 2008; Weaver & Ingram, 1969). That is, Allan's and Bergman's rules are strongly influenced by epigenetic factors, within the bounds of a species' overall phylogenetic traits.…”
Section: Discussionmentioning
confidence: 96%
“…If these observations are correct, then epigenetic factors may also be involved in the generation of characteristic regional In support of this view, it has been shown that environmental temperature irreversibly regulates appendage length and body mass at a critical time of neonatal development (Serrat, 2013;Serrat, King, & Lovejoy, 2008;Weaver & Ingram, 1969). That is, Allan's and…”
Section: Tail Length Variation As Environmental Adaptationmentioning
confidence: 94%
“…These data are consistent with older studies demonstrating reduced longitudinal growth, bone length, and tail length in experimental animals housed at sub‐thermoneutral temperatures (Al‐Hilli & Wright, ; Ashoub, ; Sumner, ; Weaver & Ingram, ). More recently, Serrat, King, and Lovejoy () and Serrat () found that mice housed at 7 °C had shorter bodies, tails, and limb bones than mice raised at 27 °C, despite higher food intake and no difference in body mass. Importantly, cold exposure reduced blood flow and solute transport to limb bone growth plates in vivo (Serrat et al, ; Serrat, Williams, & Farnum, ), whereas cold‐induced reductions in growth were mitigated by exercise (Serrat, Williams, & Farnum, ) and hindlimb heating (Serrat, ; Serrat et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bernays, 1986;Meyer, 1987;Agrawal, 2001;Marchinko, 2003;Hoverman and Relyea, 2007;Muschick et al, 2011;Svanbäck and Schluter, 2012;Serrat, 2013;Standen et al, 2014). Our experiment was designed to examine how the mammalian masticatory apparatus -represented here by a model organism, the white rabbit -responds adaptively to temporal variation in food mechanical properties at different stages of the life span.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which phenotypic sensitivity to environmental cues changes during development has been examined in a variety of species and traits (Hinton and McNamara, 1984;Meyer, 1987;Bouvier, 1988;Lieberman et al, 2001;Lieberman et al, 2003;Dufty et al, 2002;Marchinko, 2003;Taborsky, 2006;Hoverman and Relyea, 2007;Kotrschal and Taborsky, 2010;Serrat, 2013). Although these studies have documented substantial variation in how plasticity varies with age, there appears to be a general tendency for plasticity to decrease as organisms mature.…”
Section: Introductionmentioning
confidence: 99%